2009
DOI: 10.1094/mpmi-22-11-1412
|View full text |Cite
|
Sign up to set email alerts
|

SOD1-Targeted Gene Disruption in the Ericoid Mycorrhizal Fungus Oidiodendron maius Reduces Conidiation and the Capacity for Mycorrhization

Abstract: The genome sequences of mycorrhizal fungi will provide new opportunities for studying the biology and the evolution underlying this symbiotic lifestyle. The generation of null mutants at the wild-type loci is one of the best methods for gene-function assignment in the post-genomic era. To our knowledge, the generation of superoxide dismutase 1 (SOD1)-null mutants in the ericoid mycorrhizal fungus Oidiodendron maius is the first example of a gene-targeted disruption via homologous recombination in a mycorrhizal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
2
35
0
2
Order By: Relevance
“…Involvement of SOD1 in the control of morphogenetic processes has been demonstrated in other fungi, such as Neurospora crassa (Munkres 1992; Belozerskaya and Gessler 2006), S. cerevisiae (Liu et al 1992) and, more recently, in the ericoid mycorrhizal fungus O. maius (Abbà et al 2009). A significant decrease in conidiation was in fact observed in the O. maiusSOD1-null mutant.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Involvement of SOD1 in the control of morphogenetic processes has been demonstrated in other fungi, such as Neurospora crassa (Munkres 1992; Belozerskaya and Gessler 2006), S. cerevisiae (Liu et al 1992) and, more recently, in the ericoid mycorrhizal fungus O. maius (Abbà et al 2009). A significant decrease in conidiation was in fact observed in the O. maiusSOD1-null mutant.…”
Section: Discussionmentioning
confidence: 92%
“…Overall these data indicate that SOD1 expression is strongly induced in the intraradical phase of the fungus, irrespective of the plant species and fungus involved in the association. Although the precise role of this enzyme in the symbiosis remains to be ascertained, it is likely that it plays a pivotal role in the relationship of the fungus with its host plant, as it has been recently described in the ericoid mycorrhizal fungus O. maius (Abbà et al 2009). A significant decrease in the percentage of mycorrhization was in fact observed in roots colonized by the O. maiusSOD1-null mutant.…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates that the bacterium itself does not cooperate with the fungus in ROS detoxification after H 2 O 2 /GR24 treatment, but its presence and its constitutively expressed ROS-related genes contribute to the ROS homeostasis of G. margarita. A regulated synthesis of ROS has a role not only in plant communication (Gilroy et al, 2014), but also in fungal morphogenesis, growth and development, as suggested for fungi interacting with plants or animals (Abbà et al, 2009;Ryder et al, 2013;Mu et al, 2014).…”
Section: Endobacterial Impact On the Am Fungus Fitnessmentioning
confidence: 96%
“…Although antioxidation activity in plants has been measured during these symbiotic relationships, less attention has been placed on understanding the roles of antioxidation enzymes and genes in the fungal partners. In the ericoid mycorrhizal fungus Oidiodendron maius loss of SOD1 activity in the fungus increased ROS sensitivity and, importantly, reduced the capacity for the fungus to colonize host roots, suggesting redox homeostasis is important for mycorrhization (Abbà et al, 2009). It is thus important to continue to tease apart the arsenal of genes required to successfully colonize plants through molecular analysis.…”
Section: Biotrophs and Endophytesmentioning
confidence: 99%